The first zoea of Inachus aguiarii, Inachus communissimus and Ergasticus clouei (Decapoda, Brachyura, Majoidea) with implications for the systematics of the family Inachidae - Guerao, Guillermo; Abelló, Pere (Zootaxa, 2007)
The first zoeal stages of the inachid crabs Inachus aguiarii de Brito Capello, 1876, I. communissimus Rizza, 1839 and Ergasticus clouei A. Milne-Edwards, 1882, are described and illustrated from laboratory-hatched material obtained from ovigerous females collected in the western Mediterranean. The morphologies of the first zoeae were compared with the corresponding stage of other known species in the family Inachidae. The zoeae of I. aguiarii and I. communissimus are very similar to those described in other species of the genus, especially I. thoracicus and I. dorsettensis. The zoeae of I. aguiarii and I. communissimus differ from each other in the number of setae on the ventral margin of the carapace. The first zoea of E. clouei, however, does not share the zoeal characters common to other Inachidae. Therefore, does not completely fit into the characteristics of the family.